The Effectiveness of Educational Intervention in the Health Promotion in Elderly people - R (Heidari); T Khojasteh; F Hejazi; M Baradaran Eftekhari; H Malekafzali; K Falahat; T Faridi (Tehran University of Medical Sciences, 2010)
Background: More than 8% of Irans populations are elderly. The greatest challenge in this generation is improvement of health and quality of life. So we decided to perform an interventional study with the aim of promoting the health of the elderly.Methods: This study was a community interventional in Ekbatan Complex. Subjects were elderly. At first, need assessment was done with the participation of 200 elderly by questionnaire. Based on the need assessment, we designed the educational interventions in different fields such as nutrition, mental health, and exercise and then, we compared the results.Results: 0ne hundred elderly participated as interventional group. There were 86% women and 24% of men. Almost 59% were in the 60-69 age group. More than ¼ of the subjects were university graduates. Pre and post interventional groups were matched in age, education and gender. Regarding nutrition, second priority food in women aged 60-69 was rice and after the intervention, it was changed to vegetables (P= 0.05) but in other age groups and in the mens groups no difference were noted.Aerobic exercises in women has increased after the intervention (P= 0.01). With regards to mental health, life satisfaction among women under study has increased from 68% to 90% after the intervention (P= 0.01). Feeling happy most of the time has increased from 53% to 83% in women aged 60-69 (P= 0.01) and in men from 64% to 83% (P= 0.05) respectively.Conclusion: Policymakers should design long-term educational programs to promote the elderly lifestyles.